Synthesis of Zinc Nanoparticles Using Plant Extract for Broiler’s Feed Additive - cecep hidayat (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
Nanotechnology has been developed in various fields, included animal nutrition. Nanotechnology made the feed ingredient feed aditive and supplement in nano size, to expand the surface of the material, hence, its biological function in metabolic processes will be enhanced in the animal body. This paper will discuss the production of nanoparticle Zinc (Zn) by green synthesis method using phytogenic compounds from plant extracts as bioreductor and biostabilizer. The nano-Zn product is added into poultry diet as feed additive. The nanoparticle of Zn increased Zn bioavailability in broiler diet. Its utilization in lower doses is more efficient compared to conventional forms. The use of nanoparticle Zn has positive effect in improving growth performance and immunity status. The doses of nano Zn is 20-90 mg/kg, lower than the dose of non-nanoparticle form of Zn (40-120 mg/kg). Low doses will reduce production costs and decrease the amount of excreted Zn, which will reduce pollution to the environment. Zn nanoparticles are also reported to have antibacterial and antioxidant functions which will improve health performance of broilers.